Cloning of a human galactokinase gene (GK2) on chromosome 15 by complementation in yeast. - Lee, R T (1992)
A human cDNA encoding a galactokinase (EC 2.7.1.6) was isolated by complementation of a galactokinase-deficient (gal1-) strain of Saccharomyces cerevisiae. This cDNA encodes a predicted protein of 458 amino acids with 29% identity to galactokinase of Saccharomyces carlsbergensis. Previous studies have mapped a human galactokinase gene (GK1) to chromosome 17q23-25, closely linked to thymidine kinase. The galactokinase gene that we have isolated (GK2) is located on chromosome 15. The relationship between the disease locus for galactokinase deficiency galactosemia, which is responsible for cataracts in newborns and possibly presenile cataracts in adults, and the two galactokinase loci is unknown.